2013
DOI: 10.1089/scd.2011.0709
|View full text |Cite
|
Sign up to set email alerts
|

Emodin As an Effective Agent in Targeting Cancer Stem-Like Side Population Cells of Gallbladder Carcinoma

Abstract: Side population (SP) cells are previously identified from bone marrow based on their capacity to efflux of the fluorescent dye Hoechst 33342. Recent studies demonstrate that SP cells isolated from various cancer cell lines and primary tumors possess stem-cell-like properties. Thus, targeting tumor SP cells may provide new strategies for treatment in clinic. We previously showed that 1,3,8-trihydroxy-6-methylanthraquinone (emodin), a reactive oxygen species (ROS) generator, enhanced sensitivity of gallbladder c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 50 publications
1
52
0
Order By: Relevance
“…Downregulation of Wnt/b-catenin signaling was also observed in breast CSCs treated with sulforaphane, a component of broccoli and broccoli sprouts [25]. Emodin was previously reported to target the stem-like side population of gallbladder carcinoma by suppressing expression of the ATP-binding cassette superfamily G member ABCG2 [26]. Our data showed that emodin effectively suppressed the self-renewal capacity of GSCs and indicated that this occurred through suppression of critical stemness signaling pathways.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Downregulation of Wnt/b-catenin signaling was also observed in breast CSCs treated with sulforaphane, a component of broccoli and broccoli sprouts [25]. Emodin was previously reported to target the stem-like side population of gallbladder carcinoma by suppressing expression of the ATP-binding cassette superfamily G member ABCG2 [26]. Our data showed that emodin effectively suppressed the self-renewal capacity of GSCs and indicated that this occurred through suppression of critical stemness signaling pathways.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, to overcome the therapeutic resistance of CSCs, it is necessary to find compounds that target CSCs for combination therapy with conventional treatments. One promising source of CSC-targeting agents is naturally occurring dietary compounds because several reports have shown that some of these compounds affect the self-renewal capacity of CSCs [20][21][22][23][24][25][26]. In the present study, we investigated the effect of emodin, an anthraquinone compound present in rhubarb, on the biology of GSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, aldehyde dehydrogenase 1 (ALDH1), a soluble protein is used detect CSCs in various cancers, including leukaemia [37], breast cancer [38], colon cancer [39], liver cancer [40], lung cancer [41] and pancreatic cancer [42]. SP-cells, are a population of cells which are capable of efflux of Hoechst 33,342 dye, which is another non-cell-surface marker that has also been used for detection of normal stem cells as well as CSCs [43,44]. Bio-molecules used for the detection and isolation of CSCs in different cancers to date are summarised in Table 2 along their functions in normal tissues.…”
Section: Csc Markersmentioning
confidence: 99%
“…Emodin is an anthraquinone, is naturally distributed and well known to possess broad pharmacological activities [2]. Emodin (D1) has been reported to inhibit the proliferation of many cancer cells which include; Colon cancer [3] [4], breast cancer [5] [6], gall bladder cancer [7] [8], pancreatic cancer [9], lung cancer [10] [11] and human cervical cancer [12]. Poor bioavailability and toxicity in vivo have been documented to limit emodin as cancer chemotherapy [13].…”
Section: Introductionmentioning
confidence: 99%